Membangun Citra Humas Universitas Islam Negeri Sumatera Utara dalam Mewujudkan World Class University - Emia Pepayosa Br Surbakti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The study aims to determine the role of PR in building the image of the State Islamic University of North Sumatra, the supporting and inhibiting factors of Public Relations in order to build an image, and the results achieved by Public Relations in building that image. This research is a qualitative descriptive study. The results showed that the role of Public Relations in building the image of UIN SU, 1) the role of Public Relations in building the image of UIN SU, namely as a form of information built by Public Relations in building images, 2) supporting factors for the role of Public Relations, namely support from superiors, obstacles to Public Relations, namely lack of human resources who are experts in their fields, 3) The results achieved by Public Relations in order to build the image of UIN SU are the role of Public Relations of UIN SU as a relationship builder, the role of Public Relations in realizing quality universities that can meet the educational needs of the people of North Sumatra and the role of Public Relations in efforts to improve the quality of education Public.